Impact of Transport Infrastructure on Gross Regional Products: A Study on Chinese Economic Regions - Rim, Gwang-Nam; An, Chol-Ju (Finance & Economics Review, 2022)
Purpose: This study examines the impact of transport infrastructure on the Gross Regional Products in Chinese economic regions. Methods: The study analyzes the impact of transport infrastructure on the Gross Regional Products according to the eight economic regions in China by using descriptive statistics and regression analysis methods. Results: The findings are that a) densities of railways and highways have strong impacts on Gross Regional Products per capita according to Chinese economic regions, b) impacts of densities of railways and highways on Gross Regional Products per capita differ among Chinese economic regions and c) construction of new transport infrastructure has a more positive impact on Gross Regional Products per capita compared to regions with already developed transport infrastructure. Implications: Region-specific features ought to be considered in making and implementing the economic development policy according to economic regions.